(2x-y = -3 × y = 0 × (0, 0) × ( -1, 1) × (1, -1) =
(2x - y = -3 × y =0 × (0)) ×, × 0 ×, × 1 ×, × -1
Answer:
y = x^2 (x - 2) = x^3 - 2 x^2
dy/dx = 3 x^2 - 4 x
At x = 3 dy/dx = 3 * 9 - 4 * 3 = 15 The slope (gradient) of the curve
Answer:
A vertical reflection is given by the equation y=−f(x) y = − f ( x ) and results in the curve being “reflected” across the x-axis. A horizontal reflection is given by the equation y=f(−x) y = f ( − x ) and results in the curve being “reflected” across the y-axis.
Answer:
it is t
Step-by-step explanation: